Mitochondrial function evaluation in epidermal cells ex vivo after ultraviolet irradiation - Gonzalez Maglio, Daniel Horacio (2011)
Ultraviolet radiation (UVR) effects on skin have been extensively studied. However, mitochondrial dysfunction and superoxide (O2) production have only been studied using cell cultures, which are useful models, but do not consider the crosstalk between tissues or cellular differentiation. We aimed to evaluate the usefulness of fluorescent dyes to study skin ex vivo. Mitochondrial alterations were evaluated in epidermal cells isolated from UVR-exposed mice. Furthermore, a combination of dyes and antibodies was tested to analyse specific skin cell types. UVR caused a decrease in the percentage of total cells with polarized mitochondria, but did not change the mitochondrial O2 production. However, this production was increased significantly in DiOC6+ cells. Furthermore, it was possible to evaluate the cellular damage produced to basal keratinocytes and Langerhans cells. The results show that fluorescent dyes –alone or in combination with antibodies– are useful to analyse cellular events that take place in whole organs.